2020
DOI: 10.1002/asia.202000621
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Poly(ester‐enamine) from Spontaneous Amino‐yne Click Reaction for Stabilization of Gold Nanoparticle Catalysts

Abstract: Hyperbranched polymers have attracted much attention due to attractive properties and wide applications, such as drug controlled release, stimuli-responsive nano-objects, photosensitive materials and catalysts. Herein, a novel hyperbranched poly(ester-enamine) (hb-PEEa) was designed and synthesized via the spontaneous amino-yne click reaction of A2 monomer (1, 3-bis(4-piperidyl)-propane or piperazine) and B3 monomer (trimethylolpropanetripropiolate). By controlling monomer concentration, molar ratio and rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Nevertheless, it was previously shown that alkynes bearing EWGs (activated alkynes) are also suitable Michael acceptors. Indeed, the reaction between an amine and an activated alkyne is named as spontaneous amino-yne click reactions, and these reactions have been successfully adopted for various applications and the synthesis of several polymers known as poly­(enamine)­s. As the name suggests, spontaneous amino-yne click reactions are straightforward, fast, and occur spontaneously at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it was previously shown that alkynes bearing EWGs (activated alkynes) are also suitable Michael acceptors. Indeed, the reaction between an amine and an activated alkyne is named as spontaneous amino-yne click reactions, and these reactions have been successfully adopted for various applications and the synthesis of several polymers known as poly­(enamine)­s. As the name suggests, spontaneous amino-yne click reactions are straightforward, fast, and occur spontaneously at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] It also provides a solution for the synthesis of unsaturated polyester. [32][33][34][35][36][37][38][39] Moreover, the direct addition of carboxylic acid to alkynes is the most economical and widely used method. [40] The enol ester obtained by the addition of alkyne and carboxylic acid has a wide range of applications in organic synthesis, pharmaceutical chemistry and polymer construction.…”
Section: Introductionmentioning
confidence: 99%